Cost and benefit analysis of adopting climate adaptation practices among smallholders: The case of five selected practices in Ghana - Williams, Portia Adade; Karanja Ng'ang'a, Stanley; Crespo, Olivier; Abu, Mumuni (Elsevier, 2020)
Smallholder farmers mostly depend on agriculture for their sustenance yet the sector is threatened by changing climate. It is essential for smallholders to adapt to reduce their vulnerability. Estimating the economic effectiveness of climate adaptation practices would enhance planning and actions among stakeholders and consequently impact policy. This study conducted an ex-ante in-depth empirical analysis of the costs and benefits of implementing five climate adaptation strategies identified among smallholder horticultural farmers in Ghana. A total of 180 smallholder households who have implemented the identified practices in two horticultural cropgrowing municipalities were surveyed. Profitability indicators, evaluation of environmental and social externalities were employed to comparatively estimate the cost-effectiveness of the practices. The results indicated that, from private and public perspectives, implementing any of the five adaptation practices would yield positive benefits. However, considering the capital required, payback period for investments made and risks from implementation, two out of the five practices are particularly fitting choices for the smallholders. Institutional and policy support is desirable if all the practices are to be adopted. To broaden information on potential of climate adaptation vis-a-vis ` climatic effects with economic analysis, the study proposes integrating localized climate vulnerability and economic assessments for enhanced climate adaptation actions.